Development of a Supplementary Geometry Book Integrating Realistic Mathematics Education and Reog Ponorogo Ethnomathematics to Improve Elementary Students’ Numeracy Literacy - Ulum Fatmahanik; Anis Afifah; Hanin Niswatul Fauziah; Martinez David (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThis study presents the development of a supplementary geometry book for elementary students by integrating Reog Ponorogo ethnomathematics into the Realistic Mathematics Education (RME) approach to enhance numeracy literacy. The research employed a Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation instruments involved expert evaluations in content, pedagogy, media, and language, alongside practicality questionnaires and numeracy literacy assessments. The developed book achieved high validity across expert domains: 89.8% (content), 91% (media), 94% (learning), and 90% (language). Student response also indicated high practicality (82.3%). A one-sample t-test and N-gain analysis showed a significant improvement in numeracy literacy, with an N-gain score of 0.6461 (categorized as moderate), reflecting a “quite effective” level. These findings suggest that incorporating ethnomathematical elements from local culture within an RME framework can provide meaningful, contextual learning experiences and foster mathematical understanding in early-grade students.Keywords: supplementary books, realistic mathematics education, ethnomathematics, numeracy literacy.AbstrakPenelitian ini menyajikan pengembangan buku suplemen geometri untuk siswa sekolah dasar dengan mengintegrasikan etnomatematika Reog Ponorogo ke dalam pendekatan Pendidikan Matematika Realistik (RME) untuk meningkatkan literasi numerasi. Penelitian ini menggunakan metodologi Penelitian dan Pengembangan (R&D) dengan menggunakan model ADDIE (Analisis, Desain, Pengembangan, Implementasi, Evaluasi). Instrumen validasi melibatkan evaluasi ahli dalam konten, pedagogi, media, dan bahasa, di samping kuesioner praktikalitas dan penilaian literasi numerasi. Buku yang dikembangkan mencapai validitas tinggi di seluruh domain ahli: 89,8% (konten), 91% (media), 94% (pembelajaran), dan 90% (bahasa). Respon siswa juga menunjukkan kepraktisan tinggi (82,3%). Uji-t satu sampel dan analisis N-gain menunjukkan peningkatan yang signifikan dalam literasi numerasi, dengan skor N-gain sebesar 0,6461 (dikategorikan sebagai sedang), yang mencerminkan tingkat "cukup efektif". Temuan ini menunjukkan bahwa menggabungkan unsur-unsur etnomatematika dari budaya lokal dalam kerangka RME dapat memberikan pengalaman belajar yang bermakna dan kontekstual serta menumbuhkan pemahaman matematika pada siswa kelas awal.Kata kunci: buku suplemen, realistic mathematics education, etnomatematika, literasi numerasi.